The Influence of Food Vlogger Content on Culinary Consumer Purchase Decisions in Pontianak (Study on Tiktok Hobby Makan Account) - Tyas*, Heni Mulyaning; Pebrianti, Wenny (Universitas Syiah Kuala, 2024)
This study aims to analyze the influence of Hobby Makan food vlogger content with product attractiveness, interactivity and online consumer reviews (OCR) on purchase decisions with trust as an intervening variable on culinary consumers in Pontianak. This research is causal associative with a quantitative approach. The research population of TikTok users who know and follow the TikTok account of food vlogger Hobby Makan and located in Pontianak City with a sample of 150 samples selected using the purposive sampling technique. The data collection technique uses a questionnaire in the form of a Likert scale. The results showed that product attractiveness did not have a significant effect on purchase decisions, interactivity had a significant influence on purchase decisions, the influence of online customer reviews on purchase decisions was not significant, the influence of interactivity on trust was significant and positive, the influence of product attractiveness on purchase decisions was significant and positive, the influence of product attractiveness on purchase decisions was not significant, the influence of interactivity on trust was significant and positive, the influence of product attractiveness on purchase decisions was significant and positive, the influence of product attractiveness on purchase decisions was not significant, the influence of product attractiveness was not significantly affected by the purchase decision, the influence of online customer reviews on purchase decisions was not significant, the influence of interactivity on trust was significant and positive, the influence of product attractiveness on purchase decisions was significant and positive, the influence of product attractiveness was not significantly affectedOnline customer reviews on trust are significant and positive, the influence of trust on purchase decisions is significant and positive, the indirect influence of interactivity on purchase decisions through trust is not significant, and finally the results of the analysis show that online customer reviews on purchase decisions through trust have a significant influence. Keywords: product attractiveness, interactivity, online customer review, trust, purchase decision